Role of the educator and teacher in creating conditions to overcome the discontinuity between preschool and elementary school - Arsić, Zvezdan M.; Savković, Zorica N. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
At school, children spend the most beautiful period of their childhood and youth, and the moment they start school is always festive and exciting. However, it is known that school brings also the first concerns and problems. Problems and difficulties, which can occur at the beginning of schooling may, have long-term efects on the adaption and success of children, even on later adult life. The causes that lead to this situation are many and varied, and one of the most important is the educational gap in the educational system, whose essence lies in the disconnection between the various degrees of education. Taking into account the above findings, we discuss in this paper the most common causes that lead to the discontinuty between preschool and primary levels of education and areas in which the discontinuity is usually expressed. Also, the operation is determiend and focusedattention on centrain assumptions and conditions that nead to beaccompliched in order to eliminate the effects of discontinuity abd achieve the necessary continuity between the pre-school and primary school children and facilitate the transition from lower to higher levels of education.